Benin : Request for a Three-Year Arrangement Under the Poverty Reduction and Growth Facility. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 2005)
The staff report for the Request for a Three-Year Arrangement Under the Poverty Reduction and Growth Facility highlights Benin's economic developments and progress in structural reforms. Benin experienced a decade of good economic performance, but poverty reduction remains a concern. Policy discussions focused on immediate measures to stabilize and restore the fiscal situation and to obtain structural reforms. The structural reform program aims to make progress in implementing the reform agenda of the cotton sector.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet